Representation of Multiculturalism and Critical Thinking Aspects in EYL Textbook Used in a Bilingual Classroom in Indonesia - Jasmine Fadhillah; Siti Muniroh; Niamika El Khoiri (Didaktika: Jurnal Kependidikan, 2025)
Multiculturalism and critical thinking are both crucial aspects that need to be incorporated to shape students as global citizens. Thus, this research aims to find the multiculturalism and critical thinking aspects in an EYL Textbook entitled "Story Central Student Book 3" published by Macmillan Education, Used in a Bilingual Classroom in Indonesia. The research design will be qualitative, and it will make use of thematic analysis. The scope of the multicultural aspects and how it meets the needs of cultural teaching in English language teaching are revealed in this checklist. The critical thinking aspects are based on the blooms taxonomy, higher order thinking skills. The results found that this book gives opportunities for critical engagement and cultural diversities which align with 21st-century educational goals. However, further research is necessary to evaluate its effectiveness in fostering critical thinking among students using this book as the teaching and learning material, acknowledging the limitations of this study’s methodology.